Unraveling the mechanism of furfural tolerance in engineered Pseudomonas putida by genomics - Zou, Lihua; Jin, Xinzhu; Tao, Yuanming; Zheng, Zhaojuan; Ouyang, Jia (Frontiers in Microbiology, 2022)
As a dehydration product of pentoses in hemicellulose sugar streams derived from lignocellulosic biomass, furfural is a prevalent inhibitor in the efficient microbial conversion process. To solve this obstacle, exploiting a biorefinery strain with remarkable furfural tolerance capability is essential. Pseudomonas putida KT2440 (P. putida) has been served as a valuable bacterial chassis for biomass biorefinery. Here, a high-concentration furfural-tolerant P. putida strain was developed via adaptive laboratory evolution (ALE). The ALE resulted in a previously engineered P. putida strain with substantially increased furfural tolerance as compared to wild-type. Whole-genome sequencing of the adapted strains and reverse engineering validation of key targets revealed for the first time that several genes and their mutations, especially for PP_RS19785 and PP_RS18130 (encoding ATP-binding cassette (ABC) transporters) as well as PP_RS20740 (encoding a hypothetical protein), play pivotal roles in the furfural tolerance and conversion of this bacterium. Finally, strains overexpressing these three striking mutations grew well in highly toxic lignocellulosic hydrolysate, with a cell biomass around 9-fold, 3.6-fold, and 2-fold improvement over the control strain, respectively. To our knowledge, this study firstly unravels the furan aldehydes tolerance mechanism of industrial workhorse P. putida, which provides a new foundation for engineering strains to enhance furfural tolerance and further facilitate the valorization of lignocellulosic biomass.